2020
DOI: 10.1155/2020/3270530
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices about Trachoma in Rural Communities of Tigray Region, Northern Ethiopia: Implications for Prevention and Control

Abstract: Background. Trachoma is a neglected tropical disease which is the leading infectious cause of blindness in the world. Trachoma is one of the major health problems in Tigray Region, Northern Ethiopia. However, knowledge, attitudes, and practices about trachoma are not yet studied in depth. The objective of the study was to assess knowledge, attitudes, and practices on trachoma and its associated factors among rural communities in two districts of Tigay Region, Northern Ethiopia. Methods. A cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Those study subjects who had no formal education and grade 1-8 were 36.5% and 58% less likely to have adequate knowledge when compared to the counterpart, respectively. This result is consistent with study done in Kenya in which signi cant proportion of individuals who had no formal and primary education had inadequate knowledge regarding trachoma (25). The possible explanation of this nding would be the fact that people who had higher educational background had better exposure to different media and information.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Those study subjects who had no formal education and grade 1-8 were 36.5% and 58% less likely to have adequate knowledge when compared to the counterpart, respectively. This result is consistent with study done in Kenya in which signi cant proportion of individuals who had no formal and primary education had inadequate knowledge regarding trachoma (25). The possible explanation of this nding would be the fact that people who had higher educational background had better exposure to different media and information.…”
Section: Discussionsupporting
confidence: 90%
“…The present study revealed that 21%, 20.1% and 74.4% of the respondents reported correctly that trachoma can be transmitted through contact with discharges, sharing clothes or fomites and unhygienic environment, respectively. This nding is in line with studies done in Kenya in that only one third and 35% of the participants correctly knew that ies and not washing face were important predictors for the transmission of trachoma disease, repectively (25).…”
Section: Discussionsupporting
confidence: 90%
“…This result was almost similar with studies conducted in Northern Ethiopia (89.2%), Southern Ethiopia (92.6%), and Bangladesh (86%). [11][12][13] However, it is much higher than the research report from Kenya in which about 65.7% of the respondents had ever heard about trachoma. 14 This might indicate that community mobilization and sensitization has been conducted in the study sites.…”
Section: Discussionmentioning
confidence: 72%
“…In table (6) regarding the relation between total knowledge level about trachoma post educational program and personal data of the studied mothers found that more than half of them who had high knowledge level about trachoma post educational program were urban with statistically significance differences which , and more than two thirty of the studied mothers with high knowledge level about trachoma post educational program had university education, and housewife .…”
Section: Lopna R Et Almentioning
confidence: 93%
“…Personal data Table (6) presents that there were statistically significance relationship between total knowledge scores of the studied mothers post-educational program and their residence, educational levels, and occupation in which P -value was 0.05, 0.04,and 0.04.respectively.…”
Section: Table (6): Relation Between Total Knowledge Level About Trachoma Post Educational Program and Personal Data Of The Studied Mothementioning
confidence: 93%